2012
DOI: 10.1387/ijdb.120049ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of RNAi-mediated knockdown of the Bombyx mori transformer-2 gene on the sex-specific splicing of Bmdsx pre-mRNA

Abstract: In Drosophila melanogaster, transformer-2 (tra-2) is essential for female differentiation and is known to induce female-specific splicing of doublesex (dsx). The function of Bmtra-2, the Bombyx mori homolog of tra-2, on the other hand remains to be elucidated. As an initial step to learn about the biological function of Bmtra-2, we determined whether Bmtra-2 is capable of inducing the female-specific splicing of Drosophila dsx. RNAi-mediated knockdown of Bmtra-2 using Bombyx cultured cells transiently transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 28 publications
1
72
0
Order By: Relevance
“…Also, RNAi of Bmtra2 in Bombyx eggs does not affect female development but causes abnormal development of testis in males. Hence, Bmtra2 has a role in early testis morphogenesis, but it does not play a role in Bombyx sex determination [Suzuki et al, 2012].…”
Section: Tra/tra2mentioning
confidence: 95%
See 2 more Smart Citations
“…Also, RNAi of Bmtra2 in Bombyx eggs does not affect female development but causes abnormal development of testis in males. Hence, Bmtra2 has a role in early testis morphogenesis, but it does not play a role in Bombyx sex determination [Suzuki et al, 2012].…”
Section: Tra/tra2mentioning
confidence: 95%
“…Due to the selection of 3 different 3 ′ splice sites within the second intron and 2 different splice sites within the seventh intron, Bmtra2 pre-mRNA is alternatively spliced to produce 6 different isoforms. All 6 deduced BmTRA2 proteins contain 1 RNA recognition motif domain flanked by RS (Arg/Ser) domains, a typical characteristic feature of the Drosophila TRA2 protein [Suzuki et al, 2012]. RNAi-mediated knockdown of all Bmtra2 isoforms in B. mori cultured cell lines does not affect sex-specific splicing of a Bmdsx mini gene [Suzuki et al, 2012].…”
Section: Tra/tra2mentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from 3 adult females and from BmN cells using ISOGEN (Nippon Gene) according to a protocol described previously [Suzuki et al, 2012]. Poly (A)+RNA was further purified from the total RNA extracted from BmN cells using a Magnosphere Ultra Pure mRNA Purification kit (TaKaRa) according to the manufacturer's instruction.…”
Section: Rna Extraction and Rt-pcrmentioning
confidence: 99%
“…Bopp [2010] hypothesized that in Drosophila Sex-lethal has been added upstream of transformer and has taken over auto-regulation, making the TRA-CAM domain of transformer obsolete. To examine this hypothesis, we investigated the functional relationship between the TRA-CAM domain and the autoregulation of tra using an in vitro splicing assay system in cultured cells derived from the silkworm, Bombyx mori , which was originally developed in our previous study [Suzuki et al, 2012[Suzuki et al, , 2015. Our results demonstrated that TRA enriches on the male-specific exon (exon 2b) that contains putative TRA/TRA-2 binding sites (also called dsxRE) to achieve female-specific splicing of tra in the housefly as predicted by a previous study [Hediger et al, 2010].…”
mentioning
confidence: 99%